ANALISA FAKTOR MOTIVASI BERWIRAUSAHA DI ERA INDUSTRI 4.0 PADA MAHASISWA UNIVERSITAS SARJANAWIYATA TAMANSISWA YOGYAKARTA - Muh Ali Wafa; Heri Prasetyo (Journal Competency of Business, 2019)
The purpose of this study was to find out and analyze motivation factors for entrepreneurship in the industrial era 4.0 in Sarajanawiyata Tamansiswa University Yogyakarta students. The population in this study were students of the University of Sarjanawiyata Tamansiswa Yogyakarta with a sample of 100 people. The sampling technique uses the Simple Random Sampling method, which is a type of probability sampling, where the researcher selects the sample by giving equal opportunities to all members of the population to be determined as sample members. The type of data used is primary data collected using a questionnaire distributed to employees. The analytical method used is multiple linear regression with a significant level of 5% (α = 0.05). The results of this study indicate that motivation for entrepreneurship is influenced by interest in entrepreneurship, environmental factors, significant attitudinal factors where Fcount (9,747)> Ftable (2.70). Entrepreneurship motivation is each influenced by the interest in entrepreneurship where t count (3.793)> t table (1.66). Entrepreneurial motivation is influenced by environmental factors where t counts (1.582)> t table (1.66). Entrepreneurial motivation is not influenced by attitude factors where t count (-1.753) <t table (1.66). Based on the test results of the coefficient of determination (R2), it can be explained that entrepreneurship motivation is influenced by independent variables (interest in entrepreneurship, environmental factors, and attitude factors) of 21.1% while the remaining 78.9% is influenced by other factors not included in the study. This study will invite other researchers, in order to analyze the factors outside the research, because it is suggested to the next researcher to examine the reasons why entrepreneurial motivation is influenced by other factors other than the interests of entrepreneurship, environmental factors, and attitude factors.